THE CONTENT OF PROFESSIONAL INFORMATION COMPETENCE OF FUTURE TEACHERS OF MUSIC ART - Ziza Oleksandr Oleksandrovych (International Journal of Innovative Technologies in Social Science, 2022)
Today one of the main directions of art and pedagogical education in our country is the introduction of the concept of competence approach in the educational process of higher education institutions for the preparation of professional information competence of future teachers of music. In the course of training future music teachers in higher education institutions, they gain key competencies for their future professional activities, but quite often they are not enough for the entire period of work, and therefore there is a problem in retraining and advanced training of these respondents. Over the past few years in music and pedagogical education there has been a reorientation of the concepts of "education", "readiness" for "professionalism", "competence" of the future music teacher. In modern conditions, the information competence of the future teacher of music is a radically new field of activity, which is formed through the introduction into the educational process of higher education institutions of electronic and information technologies. The formation of professional information competence in future music teachers in higher education institutions is closely related to the use of motivational, operational and content-oriented activities provided by the formation and functioning of professional and pedagogical training of future teachers. It is thanks to this statement that we can consider professional information musical competence as an integral characteristic of the individual, which determines its ability to solve problems and tasks that arise in various areas of musical and artistic activities based on the use of knowledge, skills, personal experience and personal orientation. Thus, the professional information competence of the future music teacher combines the ability to work with information, the ability to solve educational problems, the ability to use interactive software on the basis of which is the implementation of applied methods combined with teaching methods that are based on individual and collective work with respondents. Nowadays, the professional use of information media is the main criterion for the formation of professional information competence of the future music teacher. This type of activity of the future teacher aims at active and creative use of knowledge and skills in the direction of information and communication technologies, which is a criterion of professional suitability of the future teacher of music art.